Bedside testing for precision pain medicine. Issue 2 (June 2021) - Reimer, Maren; Sachau, Juliane; Forstenpointner, Julia; Baron, Ralf
Abstract : Purpose of review: In recent years, the identification of therapy responders has become an increasing focus of pain research. On the basis of laboratory quantitative sensory testing, subgroups of patients were identified, which have been shown to predict treatment response. However, the high cost and time expenditure limits the use of these lab-QST protocols in clinical practice and large clinical trials. Recent findings: Recently, different bedside testing protocols were developed as easy-to-use alternative for lab-QST. In addition, patients can be subgrouped based on their symptoms by use of patient-reported outcome measures. First results suggest that these approaches can be used to stratify patients into pathophysiological-plausible subgroups predictive for treatment response. Summary: This review presents recently developed bedside approaches that can be implemented as stratification tools in future clinical trials to realize individualized pain medicine. Being complementary rather than replaceable, future studies should combine questionnaires and sensory testing and apply them prospectively in large clinical trials.